Impact of mindfulness on construction workers' safety performance: The mediating roles of psychological contract and coping behaviors. (February 2022) - Liang, Huakang; Shi, Xiaoxiao; Yang, Donghao; Liu, Kangning
Highlights: Mindfulness has significant effects on construction safety performance. Psychological contract and coping behaviors play the mediating roles. Errors, violations and safety participation have different antecedents. Abstract: This research developed and tested an integrative model regarding the effects of mindfulness on construction workers' safety performance. Both psychological contract of safety and coping behaviors were examined as mediators. Empirical data were collected from 498 construction workers in China using a detailed questionnaire. Structural equation modeling was performed to analyze the data using AMOS and Mplus. The results showed that mindful workers were likely to have higher safety performance. Psychological contract of safety had stronger mediating effects on the relationship between mindfulness and safety performance than the coping behaviors. Furthermore, this research found that mindfulness was more related to errors and violations than safety participation. Problem-focused coping primarily mediated the effect of mindfulness on safety participation, while emotion-focused coping primarily mediated the effects on errors and violations. In addition, married workers reported more operational errors; older workers were more reluctant to follow safety rules; and workers with low education level were less likely to engage in voluntary safety activities. Theoretical and practical implications and associated research limitations are also discussed in this paper.